Detection of estrogen receptor in formalin-fixed and paraffin-embedded breast carcinoma: correlation with histological patterns. - Schmitt, F. C.; Andrade, L. M.; de Lucca, L. A. (My University, 1992)
The authors studied the expression of estrogen receptor (ER) in tissues of breast carcinomas which were previously fixed in formalin and paraffin-embedded. The ER expression was correlated with several histological findings, namely grade of differentiation, tumor necrosis, desmoplasia, lymphocytic infiltration and elastosis. The ER was detected in tissues using the avidin-biotin immunoperoxidase technique associated with the H222 monoclonal antibody from Abbott. All 39 biopsies were of infiltrating ductal carcinoma of breast and 16 of them expressed ER. The statistical analysis showed that the expression of ER was correlated with histological findings of good prognosis as well differentiated carcinomas, no tumor necrosis, absence or mild lymphocytic infiltration around the tumor cells and severe elastosis.
Keywords: estrogen receptor; formaldehyde; paraffin; breast; breast carcinoma; breast tumor; chi square distribution; comparative study; female; histology; human; immunohistochemistry; metabolism; pathology; Breast; Breast Neoplasms; Carcinoma, Infiltrating Duct; Chi-Square Distribution; Comparative Study; Female; Formaldehyde; Histological Techniques; Human; Immunohistochemistry; Paraffin; Receptors, Estrogen